2022
DOI: 10.1136/bmjopen-2021-058347
|View full text |Cite
|
Sign up to set email alerts
|

HIV viral load non-suppression and associated factors among pregnant and postpartum women in rural northeastern South Africa: a cross-sectional survey

Abstract: ObjectivesWe aimed to measure the prevalence of maternal HIV viral load (VL) non-suppression and assess associated factors, to evaluate progress towards United Nations-AIDS (UNAIDS) targets.DesignCross-sectional study.SettingThe eight largest community health centres of Ehlanzeni, a rural district in northeast South Africa.ParticipantsPregnant women living with HIV (WLHIV) in their third trimester and postpartum WLHIV and their biological infants, recruited equally across all stages of the first 24 months post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 50 publications
0
13
1
Order By: Relevance
“…These numbers fall short of the 95% UNAIDS target for viral suppression. In comparison, South African studies found 14.7%–14.8% postpartum viral non-suppression [34,35]. Importantly, in our study, of the 1497 ART-eligible, only 50.0% had viral load results at month 12, and 57.3% had viral load results at month 24.…”
Section: Discussioncontrasting
confidence: 72%
“…These numbers fall short of the 95% UNAIDS target for viral suppression. In comparison, South African studies found 14.7%–14.8% postpartum viral non-suppression [34,35]. Importantly, in our study, of the 1497 ART-eligible, only 50.0% had viral load results at month 12, and 57.3% had viral load results at month 24.…”
Section: Discussioncontrasting
confidence: 72%
“…In contrast unsuppressed viral load decreases as number of children ever born increases in 2014 while the inverse was observed in 2015 (risk increases as number of birth increases). Recent study among pregnant women revealed significant association of currently breastfeeding with increase odd of viral load non-suppression [22,59].…”
Section: Discussionmentioning
confidence: 99%
“…The collective evidence from various studies 27,31,32,34,35,47,49 revealed a statistically significant association between male gender and an increased likelihood of experiencing VNS (AOR: >1, p-value <0.05) in the context of HIV. Younger age often exhibits a higher susceptibility to experiencing VNS 10,27,30,49,50 30,34 being married or cohabitating status, 43 receiving care at smaller or medium-sized health facilities 49 or private clinics.…”
Section: Socio-demographics Factorsmentioning
confidence: 99%